2002
DOI: 10.1205/026387602321143435
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Gas Hold-up in Agitated Vessels

Abstract: Previous work found the gas hold-up in a tall, 0.15 m 3 vessel, agitated by three impellers, to decrease considerably with temperature. This was attributed to either a decrease in liquid viscosity, a decrease in surface tension or a decrease in gas density. The aim of this work was to investigate the influence of gas density on the gas hold-up. First of all, it was attempted to reproduce the data found in literature. It was shown that contaminants had a significant impact on the gas hold-up. Experiments with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Also, we observe relatively higher ε g values at θ = 303 K for oxygen compared to similar conditions reported for θ = 313 K (Supporting Information, Table S1b,c). The relatively lower ε g for gases at higher θ may be attributed to the decrease in gas density at increased θ . The effect is usually prominent in the region θ = 303–323 K .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, we observe relatively higher ε g values at θ = 303 K for oxygen compared to similar conditions reported for θ = 313 K (Supporting Information, Table S1b,c). The relatively lower ε g for gases at higher θ may be attributed to the decrease in gas density at increased θ . The effect is usually prominent in the region θ = 303–323 K .…”
Section: Resultsmentioning
confidence: 97%
“…The relatively lower ε g for gases at higher θ may be attributed to the decrease in gas density at increased θ. 25 The effect is usually prominent in the region θ = 303−323 K. 26 The extent of ε g reduction usually would depend on several factors (e.g., liquid viscosity, interfacial tension, liquid density, etc.) 25,26 including the degree of agitation (N 0 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies of cold-sparged three-phase systems, involving settling particles, have been reported during the last 30 years. However, many of the processes named above are exothermic and “hot”, operating at higher temperatures, when the assumption of negligible vapor pressure is likely to be invalid. During the past decade, studies of hot gas–liquid systems have shown that hot-sparged conditions differ significantly from those in cold gassed systems. The agitator power draw is somewhat greater at higher temperatures, although bulk and micromixing times are essentially unaltered while retained gas fractions are substantially reduced. The temperature dependence of the void fraction retained in a sparged reactor was measured by Smith et al The reduction in the gas holdup over the range from 290 to 367 K could be correlated with the absolute temperature to the power −3.2.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, studies of hot gas-liquid systems have shown that hot-sparged conditions differ significantly from those in cold gassed systems. [8][9][10][11][12][13][14][15] The agitator power draw is somewhat greater at higher temperatures, although bulk and micromixing times are essentially unaltered while retained gas fractions are substantially reduced. The temperature dependence of the void fraction retained in a sparged reactor was measured by Smith et al 10 The reduction in the gas holdup over the range from 290 to 367 K could be correlated with the absolute temperature to the power -3.2.…”
Section: Introductionmentioning
confidence: 99%